2017
DOI: 10.1189/jlb.6hi0217-043r
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Science: c-Myc regulates P-selectin glycoprotein ligand-1 expression in monocytes during HIV-1 infection

Abstract: Leukocyte extravasation is a crucial feature of the normal immune response to disease and infection and is implicated in various pathologies during chronic inflammatory disease. P-Selectin glycoprotein ligand-1 (PSGL-1) is critical for leukocyte extravasation; however, despite extensive study, it remains unclear how its expression is regulated, which in turn, impedes a more precise understanding of how its expression level affects transmigration. To investigate the regulation of PSGL-1, 60 subjects, with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 80 publications
2
16
0
Order By: Relevance
“…By using the novel mouse-tropic HIV (EcoHIV) and C57BL/6 CD40L knockout mice, Connor et al demonstrated an increase in PSGL-1 gene expression during EcoHIV infection in wild-type mice that was not witnessed in CD40L knockout mice. Furthermore, pharmacologic inhibition of c-Myc demonstrated a role for this proto-oncogene in the induction of PSGL-1 transcription [2]. This work also identified the requirement for glutamate in addition to CD40L, likely functioning via an N-methyl-D-aspartate receptor-independent mechanism.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…By using the novel mouse-tropic HIV (EcoHIV) and C57BL/6 CD40L knockout mice, Connor et al demonstrated an increase in PSGL-1 gene expression during EcoHIV infection in wild-type mice that was not witnessed in CD40L knockout mice. Furthermore, pharmacologic inhibition of c-Myc demonstrated a role for this proto-oncogene in the induction of PSGL-1 transcription [2]. This work also identified the requirement for glutamate in addition to CD40L, likely functioning via an N-methyl-D-aspartate receptor-independent mechanism.…”
mentioning
confidence: 66%
“…The mechanism of PSGL-1 gene activation by cytokines and transcription factors has been largely understudied until now. The article by Connor et al [2] that accompanies this editorial provides important mechanistic insights regarding PSGL-1 induction during HIV infection, where sCD40L and glutamate are both required mechanistically (Fig. 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Discrete state network modeling facilitates prioritization of experiments by using simple logic rules such as ‘AND’ or ‘OR’ to explicitly define signal integration, enabling investigation of cross-talk and downstream events as shown in our previous studies. [46].…”
Section: Introductionmentioning
confidence: 99%